ANALISIS TATANIAGA KOPRA DI DESA BALOBONE KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH - Alzarliani, Waode (Media Agribisnis, 2018)
This research was conducted in Balobone Village, Mawasangka Sub-district, Central Buton Regency. Coconut farmers in Balobone village have problems, in addition to the low quality of copra as well as price fluctuations in a short time often occur in copra marketing so that it affects the marketing efficiency that is formed. For this reason, a comprehensive assessment of the most efficient copra marketing system needs to be carried out, so that it can provide a proportional income contribution for farmers. The objectives of this study are: (1) Knowing copra marketing channels in Balobone Village; (2) Knowing the number of costs, margins and profits received by each marketing institution involved in copra marketing in Balobone Village; (3) Analyzing copra market performance in Balobone Village through analysis of marketing margins and producer share. The sampling procedure is carried out in an institutional approach with a snowball sampling method with the amount adjusted to field conditions and research analysis needs. Marketing channel analysis is done descriptively qualitatively to see the pattern of marketing channels formed during the copra drainage process from producer farmers to exporter traders. The conclusions of the research are (1) Farmers in marketing copra produced through 2 patterns of marketing channels, namely: a. The pattern I Marketing Channels: Inter-island Traders Surabaya Big Surabaya Traders. (2) The result of Analysis of Marketing Margin 1 received by traders shows that the marketing margin of the village collecting trader is IDR 600/Kg, costs IDR 350/Kg, Profits IDR 250/Kg, while the marketing margin of the big traders in Baubau Town is IDR 3,700/kg, with the cost IDR 1,354.5/kg, the profit received is IDR 2,543.5 / kg. Pattern 2 marketing margin received by inter-island traders is IDR 4,300, with a total cost of IDR 1,354.5/Kg, with a profit of IDR 2,945.5/Kg; (3) The percentage of the price received by farmers from each of the marketing channels I patterns is 53% and the marketing channel pattern 2 is 53. Thus, the copra marketing system of the 2 marketing channel patterns formed in Balobone Village is efficient. Farmers Desa Trader Village Collectors Besar Big Traders I (Exporters); (b) Marketing Channel Pattern II: Farmers.   Keywords: Copra, marketing margins, marketing channels